Generation A : research on autism in the workplace - Giannantonio, Cristina M.; Hurley-Hanson, Amy E. (Emerald studies in workplace neurodiversity, 2022)
Generation A is the half-million individuals with Autism Spectrum Disorder (ASD) who will reach adulthood in the next decade and be ready to enter the workforce. Generation A: Research on Autism in the Workplace is the first volume in the Emerald Studies in Workplace Neurodiversity Series. The book brings together scholars, practitioners, and educators to share their research on Autism in the workplace with a particular emphasis on Generation A. This book explores ways that researchers can help facilitate finding and maintaining employment for individuals with ASD by focusing on the transition, work, and career experiences of Generation A. This volume offers researchers, educators, and practitioners several avenues for smoothing the transition from educational settings into the workplace for a generational cohort who are poised to enter the labor market, eager to work, and wish to achieve positive work and life outcomes. This book provides several contributions to both the disability literature and research on neurodiversity in the workplace, has the potential to reduce the stigma associated with ASD, change image norms surrounding ASD, and facilitate integrating individuals with ASD into the workforce. This book will be a valuable resource for individuals with ASD, organizations interested in obtaining the benefits of hiring people with ASD, and advocacy groups supporting the transition and employment needs of individuals with ASD.